(untitled) (Nordic Journal of African Studies, 2001)
Women worldwide face discriminations and subordination in the society. This subordination of women is even more pronounced in the developing countries of Asia and Africa. Several scholars (Kenig 1996; Adeyeye 1988; Howard 1985; Kazi 1995; Kumar 1993) have asserted that rural women are discriminated against in terms of employment opportunities, access to social and productive resources, education, health status and family decisions, among others. However, rural women in developing countries have been found to play an important role in agriculture and agricultural development (Kumak 1993). Indeed, Williams (1988), Mabawonku (1988) and Olawoye (1994) have all emphasized the paradox that the woman is the nutritional bedrock of human society who feeds and nurtures mankind and at the same time manages the home. Despite these realizations, the Nigerian rural women continue to suffer subordination and the ability to fully realize their potential is greatly hampered. This paper therefore examined the constraints facing rural women in a rural Yoruba Community. The data was collected through focus-group discussions, in-depth interviews and observational methods. Specifically, fourteen focus-group discussions with different groups of women and men, and ten in-depth interviews were held. Findings reveal that despite the increasing awareness of women’s education, there is still a tacit preference for the education of the male-child. Again, perhaps the greatest pattern of subordination is in the area of ’who decides what’. Findings generally revealed that males enjoy a domineering position in this area. Other problems faced by Nigerian rural women are reflected in their small volume of economic activities, female circumcision, health and rights. The paper concludes by suggesting some intervention programmes including the mobilization of resources to prepare women for leadership roles, and awareness creation about the problem facing women and indeed rural women in South-Western Nigeria.